1992
DOI: 10.1021/ma00042a002
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated ionic polyacetylenes. 5. Spontaneous polymerization of 2-ethynylpyridine in a strong acid

Abstract: 6 11o 32 * t{VUKI UULUIVftNIAIIU V ~~ 0MB NO.00418 0,01,c 'eW"'IMJ CulleCn 'C' this Collection Of sntCrn,,tOn IS esttMateo to average I hour cer rescionie. including the time lot reviewing instructioni. searching existing dataJ %orrei. , 1 ,ther,o $no Anr4.ta-ng the data needed. and cornPleting and re.-e-nq the oflect'on of infornmation, Send comments relarding this burden eitgn,.te or any other aspect of this collfti-aOr -t,~Ornat,Cn. ABSTRACT (Maximumn 200 words)The spontaneous polymerization of the acetyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…In addition to vinyl monomers, efforts have been focused on the polymerization of acetylene-type monomers in mineral matrices, e.g., in situ polymerization of 2-ethynylpyridine (2-Epy) incorporated into MMT galleries [69][70][71]. This approach is also often used to fabricate nanocomposites based on condensation-type polymers (polyamides), e.g., short-chain ω-aminoacids, β-alanine ([H 2 N-(CH 2 ) 2 COOH]), and 6-aminohex-…”
Section: Fabrication Of Hybrid Nanocomposites Via Polymerization In Tmentioning
confidence: 99%
“…In addition to vinyl monomers, efforts have been focused on the polymerization of acetylene-type monomers in mineral matrices, e.g., in situ polymerization of 2-ethynylpyridine (2-Epy) incorporated into MMT galleries [69][70][71]. This approach is also often used to fabricate nanocomposites based on condensation-type polymers (polyamides), e.g., short-chain ω-aminoacids, β-alanine ([H 2 N-(CH 2 ) 2 COOH]), and 6-aminohex-…”
Section: Fabrication Of Hybrid Nanocomposites Via Polymerization In Tmentioning
confidence: 99%
“…The highly charged nature of this polymer is evidenced by the broad, intense band at 3410 cm À1 that arises from the side group pyridinium rings and is indicative of the strong hygroscopic characteristic due to the charged nature of the side groups. This band is characteristic of all pyridine-containing conjugated polymers reported [30,43]. Fig.…”
Section: Resultsmentioning
confidence: 73%
“…4 and 470 nm for the latter. 6 The extended conjugation observed in these systems in spite of their substituted backbones is surprising and is in contrast to substituted polvacetylenes synthesized using coordination catalysts. Results obtained by us recently from modeling studies on these ionic systems using dynamic simulation " "-.…”
Section: Resultsmentioning
confidence: 93%
“…This was substantiated by comparing the calculated Dp with the experimental one determined from Mn measured by vapor pressure osmometry. 6 It was found that n can be related to Dp (within the experimental error of 20%) for up to n = 16. …”
mentioning
confidence: 72%